Role of Exosomal Non-Coding RNAs in Bone-Related Diseases - Li, Hang; Zheng, Qiyue; Xie, Xinyan; Wang, Jiaojiao; Zhu, Haihong; Hu, Haoye; He, Hao; Lu, Qiong (Frontiers in Cell and Developmental Biology, 2021)
Bone-related diseases seriously affect the lives of patients and carry a heavy economic burden on society. Treatment methods cannot meet the diverse clinical needs of affected patients. Exosomes participate in the occurrence and development of many diseases through intercellular communication, including bone-related diseases. Studies have shown that exosomes can take-up and “package” non-coding RNAs and “deliver” them to recipient cells, thereby regulating the function of recipient cells. The exosomal non-coding RNAs secreted by osteoblasts, osteoclasts, chondrocytes, and other cells are involved in the regulation of bone-related diseases by inhibiting osteoclasts, enhancing chondrocyte activity and promoting angiogenesis. Here, we summarize the role and therapeutic potential of exosomal non-coding RNAs in the bone-related diseases osteoporosis, osteoarthritis, and bone-fracture healing, and discuss the clinical application of exosomes in patients with bone-related diseases.